2016
DOI: 10.1016/j.diii.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pulmonary and coronary artery anomalies in tetralogy of Fallot using non-ECG-gated CT angiography

Abstract: Due to its reduced scanning time and high spatial resolution, non-ECG-gated CT angiography is a non-invasive imaging modality that provides accurate information on pulmonary and coronary artery anatomy in patients with TOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
3
21
0
1
Order By: Relevance
“…Jureidini et al [20] accordingly report for two adolescents that the transthoracic echocardiography images were inadequate to visualize the coronary artery anatomy. Concordance rate between coronary angiography and surgery was 50-100% [9,22,31,33] and between CT-scan and surgery 92.1-100% [17,23,24]. Six studies found additional anomalies during surgery or defined the anatomy differently than described before based on coronary angiography or CT-scan [4,5,17,26,31,33].…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 94%
See 2 more Smart Citations
“…Jureidini et al [20] accordingly report for two adolescents that the transthoracic echocardiography images were inadequate to visualize the coronary artery anatomy. Concordance rate between coronary angiography and surgery was 50-100% [9,22,31,33] and between CT-scan and surgery 92.1-100% [17,23,24]. Six studies found additional anomalies during surgery or defined the anatomy differently than described before based on coronary angiography or CT-scan [4,5,17,26,31,33].…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 94%
“…These are the anomalies with the potentially largest clinical impact if not adequately identified and were grouped for analyses as 'ACA'. During review of the ACA, it was noticed that larger than normal conus arteries and coronary arteriovenous fistulas (CAVF) were also systematically described in several studies [5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. The conus artery (also called infundibular artery) is the first anteriorly departing branch of the RCA; it may also originate from a separate ostium in the right sinus of Valsalva (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative diagnosis of ACA is usually made with echocardiography if it is performed by senior cardiologists. Computed tomography is a non-invasive imaging technique with high sensitivity and specificity for CA anatomical analysis, but cardiac catheterization remains the gold standard for accurate coronary diagnosis, although it is not mandatory before surgery [4,5,7,20]. We do not recommend mandatory computed tomography imaging when ACA is suspected (because it would not change the indication for surgery) except for patients who had a palliative operation elsewhere without a specific description of the coronary anatomy at first surgery.…”
Section: Tetralogy Of Fallot and Abnormal Coronary Arterymentioning
confidence: 99%
“…arter anomalileri bu grup hastaların %5'inde görülür (16,17). Cerrahi prosedürü en sık etkileyen anomali, sol ön inen koroner arterin anormal olarak sağ koroner arterden çıkıp sağ ventrikül çıkım yolunu çaprazlayarak seyretmesidir (17,18). Hastalarımızdan 1 tanesinde sol koroner arterin sağdan çıktığını gözlemledik sağ ventrikül çıkım yolunu çaprazlamadığı için cerrahi açıdan risk oluşturmadı.…”
Section: Koronerunclassified